Tata Kelola Badan Usaha Milik Desa (BUMDes) Di Kabupaten Banyuasin - Mister Candera; Kosim Kosim; Seprina Seprina (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
This study aims to determine the Badan Usaha Milik Desa (BUMDes) management in Banyuasin Regency (Case Study on BUMDes Gasing Sejahtera, Gasing Village, Kecamatan. Talang Kelapa). The method used is the descriptive qualitative method. The results showed that since its establishment until now BUMDes Gasing Sejahtera has experienced very significant developments. BUMDes is engaged in “Pasar Desa” management. BUMDes Gasing Sejahtera is included in the BUMDes pilot category and financial reporting is included in the best category in Banyuasin Regency. However, BUMDes is not yet fully capable of developing other business fields. The economic and natural potentials are still not optimally managed.